Pengaruh Status Gizi Ibu Hamil Trimester III dalam Pengeluaran Kolostrum - Ciselia, Dewi (JURNAL KESEHATAN TERAPAN, 2023)
Pregnancy causes the growth of energy and nutrients, this increase is needed for fetal growth anddevelopment, KEK deficiency of nutrients can cause fetal disorders. The nutritional status of pregnantwomen needs attention because it is very influential on the colostrum contest. The purpose of thisstudy was to determine the effect of maternal nutritional status in the third trimester of pregnancy oncolostrum expenditure. Methods this study used a quantitative research method with an analyticalsurvey research method with a cross sectional design. The sample in this study was 30 respondents.The results showed that there was a relationship between nutritional status based on LILA andcolostrum expenditure in third trimester pregnant women at the Sei Baung Health Center Palembangin 2021 with p value 0.032 (≤0.05) and there was a relationship between nutritional status based onbody weight and colostrum expenditure in third trimester pregnant women. at the Sei Baung HealthCenter Palembang in 2021 with a p value 0.037 (≤0.05). It is hoped that the Puskesmas can providecounseling by developing KIE and counseling regarding nutritional needs during pregnancy and canalso provide additional food for pregnant women who suffer from malnutrition and low body weight sothat the nutritional status of pregnant women can obtain good nutritional status during pregnancy andgood colostrum contests.